Technology Transfer from British to Vietnamese Industrial Companies: Venturing into a New Business Culture - Ca, Tran Ngoc (VNU Journal of Science: Policy and Management Studies; Vol 34 No 2DO - 10.25073/2588-1116/vnupam.4147, 2018)
The paper examines the process of technology transfer from British industrial companies to Vietnamese companies focusing on the obstacles to this process, especially in different business culture environments. The study uses the case study method, conducting interviews with ten companies operating in oil and gas service industry; a civil engineering consultant company is examined for comparison. The paper argues that the differences in the perception of the same operation activity, like service in oil and gas industry, are crucial factors to take into account if the transfer process is to be successful. Also, the transferor and the recipient may have different behaviour in negotiating and in communicating with each other. Thus, the preparation of background information, doing the "home work", patience and pro-active attitudes in trying to understand partners are important for transferring technology into a different business environment. In addition, the factors, sometimes not really technology-related, such as internal political motives and organisational issues of the firms involved, can be very influential in the success of technology transfer process. Keywords: Technology transfer, business culture, learning organization.